Efektifitas Media Pembelajaran Berbasis Smartphone Untuk Mengembangkan Sikap Peduli Lingkungan Peserta Didik : (The Effectiveness of Smartphone Based Learning Media to Develop Attitudes Caring for Students 'Environmental) - Calvin Talakua; Centhya Victorin Maitimu (BIODIK, 2020)
This study aims to describe the effectiveness of using smartphone-based learning media on ecosystem materials in developing students' environmental care attitudes. The population of this study were students of class X SMA Negeri 1 Seram Utara Barat even semester 2019/2020 academic year. The number of students was 24 people. This research includes pre-experimental research using the One Group Pretest-Posttest Design. Learning using smartphone-based media is carried out four times face to face and one time giving the final test (posttest). The instrument used in this study was a questionnaire for students' environmental care attitudes. The results showed that the effectiveness of the use of smartphone learning media on ecosystem material from the average value of the questionnaire for environmental care attitudes of students reached 80 in the cultural category. The N-gain calculation is 0.60 in the medium category. The Paired Sample T-test resulted in a significance level of 0.00 <0.05 (effective). This shows that between the pre-test before using smartphone learning media on ecosystem material and the post-test after using smartphone learning media experiences a significant difference. Based on the results of several tests it is concluded that smartphone learning media on ecosystem material is effective in developing environmental care attitudes of SMA Negeri 1 students. North West Seram. Abstrak. Penelitian ini bertujuan mendeskripsikan keefektifan dari penggunaan media pembelajaran berbasis smartphone pada materi ekosistem dalam mengembangkan sikap peduli lingkungan siswa. Populasi penelitian ini adalah peserta didik kelas X SMA Negeri 1 Seram Utara Barat tahun ajaran 2019/2020 semester genap. Jumlah peserta didik sebanyak 24 orang. Penelitian ini termasuk penelitian pra-eksperimental menggunakan One Group Pretest-Posttest Design. Pembelajaran menggunakan media berbasis smartphone dilaksanakan empat kali tatap muka dan satu kali pemberian tes akhir (posttest). Instrumen yang digunakan dalam penelitian ini adalah angket sikap peduli lingkungan siswa. Hasil penelitian menunjukkan bahwa keefektifan penggunaan media pembelajaran smartphone pada materi ekosistem dari nilai rata â€“ rata angket sikap peduli lingkungan peserta didik mencapai 80 dengan kategori membudaya. Perhitungan N-gain adalah 0,60 dengan kategori sedang. Uji Paired Sample T-test memperoleh hasil tingkat signifikansi 0,00 < 0,05 (efektif). Hal ini menunjukkan bahwa antara pre-test sebelum menggunakan media pembelajaran smartphone pada materi ekosistem dan post-test setelah menggunakan media pembelajaran smartphone mengalami perbedaan yang signifikan Berdasarkan hasil beberapa uji disimpulkan bahwa media pembelajaran smartphonepada materi eksosistem Â efektif dalam mengembangkan sikap peduli lingkungan siswa SMA Negeri 1 Seram Utara Barat.